Domi Suae Quilibet Rex - Zarankaitė, Toma (Lietuvos istorijos studijos, 2017)
(about the thesis of Neringa Dambrauskaitė „Noble household in the Grand Duchy of Lithuania in the 16th century and the first half of the 17th century“)